Influence of River Valleys on Genetic Diversity and Species Distribution Patterns of Cyprididae (Crustacea: Ostracoda) on the Tibetan Plateau - Qing Hu; Bingkuan Zhu; Zhihang Ma; Yini Yang; Zhixiong Deng; Shaoqing Wen; Xiaolin Ma (Ecology and Evolution, 2025)
ABSTRACT River valleys are recognized as significant ecological barriers that impact gene flow between species adapted to distinct habitat types. The Tibetan Plateau, with its diverse habitats intersected by numerous river valleys, serves as a focal point for biodiversity research. Although previous studies have focused on plants and terrestrial animals, research on the genetic diversity of aquatic species influenced by river valleys in the Tibetan Plateau is limited. In this study, we utilized mitochondrial and nuclear genetic markers to examine variations in species composition and biodiversity among 18 Cyprididae communities (106 individuals) on the Tibetan Plateau, separated by three distinct river valleys: the Zhajia Zangbu River, the Nujiang River, and the Yarlung Zangbo River. Our phylogenetic analysis based on COI sequences revealed that the sampled communities are clustered into three genetic branches, which correspond to nine clades including two cryptic lineages. Among the 15 communities analyzed, eight exhibited mitochondrial‐nuclear discordance, indicating complex evolutionary dynamics such as hybridization or incomplete lineage sorting. Furthermore, significant differences in species composition and genetic diversity were observed among the three river valleys, potentially influenced by altitude and other environmental factors. This study offers new insights into the genetic diversity and species distribution of Cyprididae on the Tibetan Plateau, highlighting the role of geographical isolation induced by river valleys in shaping regional endemism and contributing to a broader understanding of biogeographical barriers in aquatic species.